Influência da dissipação viscosa na transferência de calor em tubos concêntricos no escoamento turbulento - Silva, Luiz Armando Gonzalez da (1977)
The temperature profile for a turbulent flow, of a newtonian fluid flowing between two concentric tubes has been determined. The velocity profile was based on the Deissler and Quarmby equations for turbulent flows. The momentum difusivity equation for the turbulent flow has been evaluated according o Deissler and Quarmby and the heat difusivity equations and represented according to Aser and Chao. These equations with the corresponding boundary conditions has beem solved employing the numerical method of Crank-Nicholson. The influence of the dissipation on the temperature profile is pronounced in the turbulent flow in the neighborhood of the inner and outer wall of the tube and increases in the axial direction.